Structures with BŪDAMAS: their semantics and morphosyntactic marking - Vaičiulytė-Semėnienė, Loreta (Lietuvių kalba, 2010)
The paper discusses half-participle structures where the half-participle of būti (‘to be') functions as a copula. The discussion is based on extensive typological linguistic research and universal grammatical hierarchies. Such structures function as free secondary predicates: either as (a) depictives or as (b) circumstantial predicates, cf. (a) Kalanta mirtį pasirinko būdamas devyniolikmetis (‘Kalanta Nom [his] death Acc chose being Nom a nineteen-year old Nom'); (b) Būdamas mažas ganė gyvulius (‘Being Nom small Nom [=a child] [he] pastured herds Acc'). Typically, in unmarked cases, circumstantial predicates are used (but not confined to the position) before the main predicate thus constituting part of a sentence and (or) analytically. Depictives, however, tend to occur after the main predicate and are encoded as a bare case.
Keywords: none